FUNGSI DAN MAKNA MANTRA DALAM TRADISI BALENGGANG MASYARAKAT DAYAK BAKATI’ RARA DI DESA SEBUNGA KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - Katerina Dora; Yohanes Bahari; Fatmawati Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research is entitled "The Function and Meaning of Mantras in the Balenggang Tradition of the Dayak Bakati' Rara Community in Sebunga Village Sajingan Besar District Sambas Regency". The general problem in the research "How is the Function and Meaning of Mantras in the Balenggang Tradition of the Dayak Bakati' Rara Community in Sebunga Village, Sajingan Besar District, Sambas Regency". This study aims to determine the types, functions and meanings of mantras in the Balenggang tradition of the Dayak Bakati' Rara community in Sebunga Village, Sajingan Besar District, Sambas Regency. The form of research used in this research is qualitative research with descriptive research methods. The data collection techniques used are interviews and documentation, while the data collection tools used are interview and documentation guides, the analytical techniques used are data reduction, data presentation, and conclusion drawing. The results of this study indicate that traditional medicine through the Balenggang tradition is still carried out by the people of Sebunga Village in healing diseases, In this study, there are ten types of spells uttered by the Balenggang shaman, the spell is still recognized and trusted by the community as a form of cultural heritage handed down by ancestors.Data analysis shows that the Balenggang mantra array contains a function as a projection system or a shaman's wishful thinking, a function as a cultural certifier, while the meanings contained in the mantra are religious meaning and social meaning.Keywords: Balenggang Mantra, Function, and Meaning